2010
DOI: 10.2174/156800910793605785
|View full text |Cite
|
Sign up to set email alerts
|

DNA Topoisomerase II Enzymes as Molecular Targets for Cancer Chemotherapy

Abstract: DNA topoisomerase II enzymes regulate essential cellular processes by altering the topology of chromosomal DNA. These enzymes function by creating transient double-stranded breaks in the DNA molecule that allow the DNA strands to pass through each other and unwind or unknot tangled DNA. Because of the integral role of topoisomerases in regulating DNA metabolism, these enzymes are vital for cell survival. Several clinically active antitumor agents target these enzymes. Mammalian cells contain two topoisomerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 0 publications
1
48
0
Order By: Relevance
“…3c, the supercoiled DNA was completely converted to the relaxed DNA in the presence of the nuclear extracts from untreated K562 (lane 2), indicating the constitutive activities of topoisomerases in the nuclei. However, only part of the supercoiled DNA was converted to the relaxed DNA in the presence of the nuclear extracts from riccardin D-treated K562 cells (lanes [3][4][5]. This result suggested that topo II activity in riccardin D-treated K562 cells was suppressed.…”
Section: Riccardin D Suppresses Topo Ii Activitymentioning
confidence: 95%
See 1 more Smart Citation
“…3c, the supercoiled DNA was completely converted to the relaxed DNA in the presence of the nuclear extracts from untreated K562 (lane 2), indicating the constitutive activities of topoisomerases in the nuclei. However, only part of the supercoiled DNA was converted to the relaxed DNA in the presence of the nuclear extracts from riccardin D-treated K562 cells (lanes [3][4][5]. This result suggested that topo II activity in riccardin D-treated K562 cells was suppressed.…”
Section: Riccardin D Suppresses Topo Ii Activitymentioning
confidence: 95%
“…Currently available topo II targeted drugs include topo II poisons and catalytic inhibitors. Topo II poisons such as etoposide, doxorubicin, anthracyclines, ciprofloxacin, and m-AMSA induce topo II-DNA complexes, inhibit resealing of DNA breaks and then trigger cell death [2,3]. Catalytic inhibitors, such as aclarubicin, inhibit the enzyme's binding to its DNA substrate or lock the homodimeric topo II in the form of a closed bracelet surrounding DNA at the post-religation step [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds take part in cancer inhibition via prevention of enzyme topoisomerase activity which is involved in DNA imitation, inducing apoptosis and expression of p53 gene (61,62). However, alkaloids have long been existed before humans; some of them are structurally similar to neurotransmitters present in the central nervous system of humans.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Topo II is vital for cell survival, and tumor cells always exert an abnormal Topo II activity. Thus, Topo II is a promising molecular target for cancer chemotherapy (10). In fact, some Topo II inhibitors, such as etoposide (VP-16) and teniposide (VM-26), have been used to treat various cancers for many years (11).…”
Section: Cholesteryl Ester Transfer Protein (Cetp) Transfers Cholestementioning
confidence: 99%